Effect of supplementation with lake soil on the growth of Arsi sheep - Kurtu, M.Y.; Ido, D.; Mukasa-Mugerwa, E. (Institute of Agricultural Research, 1991)
Investigates the mineral composition of lake soils drawn from Lakes Ziway, Shala and Abiata in Ethiopia, traditionally believed to improve production and reproduction of both cattle and sheep; tests their efficacy as a mineral supplement for Arsi sheep growth; voluntary feed intake and weight gain of sheep were major parameters under investigation.